Body composition, energy expenditure and food intake in brazilian fashion models - Mauro Fisberg; Sérgio Tufik; Marco Túlio de Mello; Alexandra Magna Rodrigues; Isa de Pádua Cintra; Luana Caroline dos Santos (Universidade Federal de Santa Catarina, 2009)
The objective of this study was to compare body composition, resting metabolic rate (RMR) and food intake between adolescent fashion models and non-models. Thirty-three models and 33 non-models ranging in age from 15 to 18 years and matched for age and BMI participated in the study. Body composition was evaluated by plethysmography. RMR was determined using an indirect calorimetry method and food intake was evaluated based on three-day food records obtained on alternate days. No significant difference in mean body fat percentage was observed between groups (p>0.05). However, when the adolescents were classified according to body fat percentage, none of the models presented a body fat percentage lower than 15%, whereas 15.2% of the non-models presented a low body fat percentage (p0.05). Mean energy intake was 1480.93 ± 582.95 kcal in models and 1973.00 ± 557.63 kcal in non-models (p=0.001). In conclusion, most models presented a body composition within the limits considered to be normal for this phase of life. RMR was similar in the two groups. However, energy intake was lower among adolescent models compared to non-models.